Anthropotechnical Interregnum - Quaresma, Alexandre (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The central aim of this article is to reflect critically about current conditions anthropotechnical of humani-ty, something analogous to the state of the art in current technological interface with emerging social realities, and their prospects horizons concerning social conjunctions that are constructed by technological means, paying particular attention to exponential technoscientific developments of Modernity and Post-modernity, these events that cause a sudden change in how we perceive the reality around us and circumscribes, redefining it radically. We will also try to demonstrate that, in fact, determine our technologies to conceive them and Plasma them socially but also just being equally and in opposite direction, determined by these fields important of societal life, since technical and structural technologies (such as genetics, cloning, the bioengenheiramento and transgenias, for example) are interfering deeper in our daily lives, to the point extraordinary and ambiguous they can even determine the biomolecular structure of our carnal constitution, or is, until something reckless and social bioethically talking. We will also launch poignant light on the question of indetermination in relation to the future societies and technologies and the endless and overdeterminations determinism they impose to each other in order to influ-ence mutually back-to extreme peculiarity and plasticity; remembering that the second (technologies) are (and will be) contained in the first (societies), as there could be, and that we humans, so even just getting influences and important deter-minations of both forces and entities. It is also worth noting that there is, in this context, a blatant lack of technologies and technosciences we produce and use, and it is then that we now turn.